Perspectives for Applications of Quantum Imaging - Basset, Marta Gilaberte; Setzpfandt, Frank; Steinlechner, Fabian; Beckert, Erik; Pertsch, Thomas; Graefe, Markus (Laser & Photonics Reviews, 2019)
Quantum imaging is a multifaceted field of research that promises highly efficient imaging in extreme spectral ranges as well as ultralow-light microscopy. Since the first proof-of-concept experiments over 30 years ago, the field has evolved from highly fascinating academic research to the verge of demonstrating practical technological enhancements in imaging and microscopy. Here, the aim is to give researchers from outside the quantum optical community, in particular those applying imaging technology, an overview of several promising quantum imaging approaches and evaluate both the quantum benefit and the prospects for practical usage in the near future. Several use case scenarios are discussed and a careful analysis of related technology requirements and necessary developments toward practical and commercial application is provided.
CRIS-Team Scopus Importer:2023-04-20
Keywords: entangled photon pairs; ghost imaging; quantum imaging; quantum microscopy